Analisis kemampuan berpikir kritis peserta didik ditinjau dari gaya berpikir pada pembelajaran ppkn menghargai keragaman di sekolah dasar - Fifi Khoirunni'ma; Matsuri Matsuri; Hasan Mahfud; Anesa Surya (Didaktika Dwija Indria, 2024)
This research aims to describe students' critical thinking abilities in terms of thinking styles when learning civic education about identity and my environment in class V of Panularan State Elementary School for the 2023/2024 academic year. This research uses a qualitative approach with a case study method. The subjects of this research were the class teacher and 12 students. This research uses questionnaire techniques, interviews, observations and documents as complements. Testing the validity of the data uses triangulation of sources and techniques. The data analysis model uses the Creswell model. The results show that there are four types of students' thinking styles, namely skuensial konkret, skuensial abstrak, acak abstrak, and acak konkret. The critical thinking abilities of class V students in terms of thinking styles in PPKn learning material respect diversity have their own characteristics. Every thinking style possessed by students has a tendency towards an indicator. This research focuses on the characteristics of thinking styles towards the level of critical thinking in Civics so that it can be used as a reference for classifying students in the Civics learning process. The implication of this research is that it can add insight regarding certain tendencies possessed by one thinking style and another in using their thinking abilities